Descriptions of the pupae of three Psychodinae species (Diptera, Psychodidae) from Argentina - Omad, Guillermo Hugo (2013)
The pupae of Alepia montana Bravo, Alepia truncata Bravo, Lago & Castro and Psychoda simillima Tonnoir, belonging to the subfamily Psychodinae, are described and illustrated. The pupae of A. montana and A. truncata were collected in tree holes in the city of San Ramón de la Nueva Orán, Province of Salta and the pupa of P. simillima in small pool on the nameless stream near El Hoyo city, Province of Chubut, Argentina. The pupa of P. simillima is similar to other pupae of the genus Psychoda, being distinguished by some features in the last segment and by respiratory trumpet. These are the first pupae described of any species of the genus Alepia.